Availability and Profit Analysis of Gas Turbine System using Fuzzy Trapezoidal Numbers with Different Left Height and Right Height - Meenu Goel , Shiv Narain, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper analyzed a gas turbine system by using method of α-cuts coupled with trapezoidal fuzzy numbers of different left and right height for general distribution.Gas turbine system having six subsystems namely - Air inlet subsystem, Compressor subsystem, Combustion chamber subsystem, Turbine subsystem, Electric generator subsystem and Governing subsystem which are working in series. Subsystems turbine, electric generator and governing fails completely via reduced capacity. Fuzzy failure and fuzzy repair rates of all the subsystems are taken as general. Giving particular values to various parameters and costs, the numerical results for availability and profit are obtained by considering exponential, Rayleigh and Weibulldistributions for all random variables.